1989
DOI: 10.1080/00986448908940348
|View full text |Cite
|
Sign up to set email alerts
|

Gas Holdup and Heat Transfer From Immersed Surfaces in Two- And Three-Phase Systems in Bubble Columns

Abstract: Two experimental slurry bubble column facilities comprising of 10.8 and 30.5 ern diameter columns and appropriate for conducting hydrodynamic and heat transfer studies arc described. The average and local gas holdup data are reported for the air-water system as a function of air velocity. The holdups for th" three phases are also reported for the air-water-glass beads system over a range of air velocity values.. The air holdup data are compared with the predictions of some of the commonly used correlations. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…Due to the excellent mixing in the bubble column, there is a negligible radial temperature gradient [23] and essentially zero resistance to radial mixing. Though temperature gradients have been observed in the vertical direction in industrial bubble columns [24], the depth of the liquid used in this experiment is only about 1-10% of the height of a typical bubble column.…”
Section: Heat and Mass Transfer Modelmentioning
confidence: 99%
“…Due to the excellent mixing in the bubble column, there is a negligible radial temperature gradient [23] and essentially zero resistance to radial mixing. Though temperature gradients have been observed in the vertical direction in industrial bubble columns [24], the depth of the liquid used in this experiment is only about 1-10% of the height of a typical bubble column.…”
Section: Heat and Mass Transfer Modelmentioning
confidence: 99%
“…For bubble columns and slurry bubble columns, gas holdup has been found to increase with increasing superficial gas velocity (Kim et al, 1972;Koide et al, 1984;Fan et ai. 1987;Saxena et al, 1989Saxena et al, , 1990a. In the dispersed bubble 80w regime, this increase has been found to be proportional to surperfïcal gas velocity (Bach and Pilhofer, 1978;Lockett and Kirkpaûick, 1975;Kara et al, 1982 Wolff et al, 1990) reported that high superficial gas velocity, higher solids concentrations and particle densities resulted in larger bubbles and consequently lower gas holdup.…”
Section: Effeets Of Gas Veloeitymentioning
confidence: 99%
“…The influence of slurry concentration on heat transfer coefficient has been investigated by Kolbel et al (1958Kolbel et al ( , 1960, Deckwer et al (1980) and Saxena et al (1989Saxena et al ( , 1990a,…”
Section: Eff't Of Liquid Viscositymentioning
confidence: 99%
See 2 more Smart Citations